2011
DOI: 10.5194/nhess-11-2173-2011
|View full text |Cite
|
Sign up to set email alerts
|

Response of the ionospheric electron density to different types of seismic events

Abstract: The electron density data recorded by the Langmuir Probe Instrument (ISL, Instrument Sonde de Langmuir) onboard the DEMETER satellite have been collected for nearly 4 yr (during 2006–2009) to perform a statistical analysis. During this time, more than 7000 earthquakes with a magnitude larger than or equal to 5.0 occurred all over the world. For the statistical studies, all these events have been divided into various categories on the basis of the seismic information, including Southern or Northern Hemisphere e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The distance occurrence of the ionospheric perturbations before earthquakes is consistent with the statistical study by He et al (). In their analysis, the result shows that there are anomalies close to the epicenters prior to the occurrence of earthquakes.…”
Section: Discussionsupporting
confidence: 91%
“…The distance occurrence of the ionospheric perturbations before earthquakes is consistent with the statistical study by He et al (). In their analysis, the result shows that there are anomalies close to the epicenters prior to the occurrence of earthquakes.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the anomaly may have been caused by other reasons. He et al (2011) and Le et al (2011) statistically studied pre-earthquake ionospheric anomalies using different methods. They found that anomalies occurring before deep focus earthquakes had smaller intensity and occurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding ionospheric effects were also observed in the magnetically conjugated region, but both the probability and amplitude are lower than those near the epicenter region. Based on electron density recorded by the DEMETER satellite during 2006, He et al (2011 also reported that the electron density increased close to the epicenters both in Northern and Southern Hemisphere. Moreover, they found that the intensity of the anomalies was enhanced when the magnitude increased and was reduced when the depth increased, which is consistent with the results of Le et al (2011).…”
Section: Statistical Studiesmentioning
confidence: 91%